Time-Resolved Contrast-Enhanced MR Angiography of Spinal Vascular Malformations - Amarouche, M. (AJNR Am J Neuroradiol, 2015)
BACKGROUND AND PURPOSE: The diagnosis of spinal vascular malformations may be challenging on conventional MR imaging because neither the location of the signal abnormality in the spinal cord nor the level of the abnormal flow voids correlates with the level of the fistula. We conducted a retrospective evaluation of the utility of using a time-resolved imaging of contrast kinetics sequence in the diagnosis, characterization, and localization of spinal vascular malformations, comparing it with the criterion standard of spinal DSA. MATERIALS AND METHODS: Fifty-five consecutive patients with a suspected diagnosis of spinal vascular malformation underwent time-resolved imaging of contrast kinetics followed by spinal DSA. All scans were performed on a 1.5T scanner by using a standard 8-channel spine coil and were reported by a neuroradiologist before the DSA was performed. RESULTS: Forty-seven lesions were confirmed on time-resolved imaging of contrast kinetics and classified as spinal dural arteriovenous fistulas (n = 33, with 1 patient having a type Ib fistula), perimedullary spinal cord arteriovenous fistulas (n = 10), and intramedullary arteriovenous malformations (n = 3). One patient had an extradural spinal vascular malformation. Time-resolved imaging of contrast kinetics identified the location of the arterial feeder to within 1 vertebral level in 27/33 patients (81.8%) with spinal dural arteriovenous fistulas and correctly predicted the side in 22/33 (66.6%) patients. Perimedullary spinal cord arteriovenous fistulas were erroneously considered to represent spinal dural arteriovenous fistulas before spinal DSA. The anatomy of the arterial supply to intramedullary arteriovenous malformations was also poorly characterized on time-resolved contrast-enhanced MR angiography. CONCLUSIONS: It has been our experience that time-resolved imaging of contrast kinetics is a useful confirmatory tool when a spinal vascular malformation is suspected on the basis of clinical and conventional MR imaging findings. As experience with the technique grows and sequences are refined, it may be possible to rely on time-resolved imaging of contrast kinetics as a screening tool for the diagnosis of spinal vascular malformations.